Tales to keep you up at night - Poblocki, Dan (Penguin Workshop, 2022)
Ignoring a handwritten warning from her grandmother, Amelia reads an old book she finds in the attic, and as elements from the stories begin to come to life around her, she realizes that she may be in a spooky story of her own.